On Modifications of Continuous and Discrete Maximum Principles for Reaction-Diffusion Problems (Advances in Applied Mathematics and Mechanics, 2011)
In this work, we present and discuss some modifications, inthe form of two-sided estimation (and also for arbitrary source functionsinstead of usual sign-conditions), of continuous and discrete maximum principles forthe reaction-diffusion problems solved by the finite element and finite differencemethods.